# How do you solve #-3x+7=3x-11#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve -3x + 7 = 3x - 11, first, you need to isolate the variable x. Start by moving all terms involving x to one side of the equation and constants to the other side. Then, combine like terms and solve for x.

Add 3x to both sides:

-3x + 3x + 7 = 3x - 3x - 11

This simplifies to:

7 = 6x - 11

Add 11 to both sides:

7 + 11 = 6x - 11 + 11

This simplifies to:

18 = 6x

Finally, divide both sides by 6:

18 / 6 = 6x / 6

This simplifies to:

3 = x

So, x = 3.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7